Isolation of IPN virus serotype VR-299 from turbot in Europe - Novoa, Beatriz; Toranzo, A. E.; Dopazo, C. P.; Barja, J. L.; Figueras Huerta, Antonio (Inter Research, 1993)
5 pages, 2 figures, 1 table.-- Note Serological and molecular properties of 2 birnavlruses isolated from Norwegian turbot Scophthalmus maximus were examined. The viral RNA and polypeptides patterns, as well as neutralization test results, showed that these strains were closely related to infectious pancreatic necrosis virus, serotype VR-299. Infectivity trials indicated no pathogenicity for turbot. This is the first isolation in Europe of VR- 299, the common North American virus strain of IPNV This work was supported by Grants MAR 89-0270 and AGF-93-0769-C02-02 from the Direccion General de Investigacion Cientifica y Tecnica (CICYT) and XUGA 20008A-91 from Xunta de Galicia, Spain Beatriz Novoa acknowledges the Ministerio de Educacion y Ciencia (Spain) for research fellowship Peer reviewed